Neuropathological Landscape of Repetitive Brain Trauma and CTE in Modern Sport - Przepióra, Agnieszka; Żmigrodzka, Anna; Kamińska, Agnieszka; Orłowska, Maria; Czernic-Goławska, Klaudia; Kozłowska, Jana; Sanocka, Maria; Falana, Joanna; Wielogórska, Aleksandra; Kwiatkowska, Anna; Trojnar, Karolina (Quality in Sport, 2026)
Background: Repetitive brain trauma has become a significant problem in modern sport, particularly in athletes exposed to repeated head impacts. Such injuries have been associated with chronic traumatic encephalopathy (CTE), a progressive neurodegenerative disease characterized by abnormal accumulation of hyperphosphorylated tau protein and other neuropathological changes. Aim: The aim of this study was to review current scientific knowledge on the neuropathological consequences of repetitive brain trauma in athletes, with particular emphasis on chronic traumatic encephalopathy. Material and methods: This study was conducted as a literature review. Relevant research articles related to repetitive brain injury and chronic traumatic encephalopathy (CTE) were identified through a PubMed database search using the following keywords: chronic traumatic encephalopathy, repetitive brain trauma, traumatic brain injury, neuropathology, and contact sports. The selected publications were analyzed to summarize the current state of knowledge on the neuropathology of CTE. Results: The reviewed studies indicate that repetitive head impacts can lead to progressive neurodegenerative changes, including abnormal tau protein deposition, neuroinflammation, neuronal loss, and axonal damage. These neuropathological alterations are considered key features of chronic traumatic encephalopathy. Conclusions: Repetitive brain trauma may significantly contribute to the development of chronic traumatic encephalopathy. Further research is needed to improve early diagnosis, prevention strategies, and clinical treatment of athletes exposed to repeated head impacts.